A child at gunpoint : a case study in the life of a photo - Raskin, Richard 1941- (Aarhus Univ. Press, 2004)
A close look at the photograph -- The origins of the photo : The Stroop Report -- The photograph in context -- Identities -- The role of the photograph in selected works of art -- Palestinian parallels? : uses of the photo in a war of images.